2004
DOI: 10.14507/epaa.v12n73.2004
|View full text |Cite
|
Sign up to set email alerts
|

The Balance Between Higher Education Autonomy and Public Quality Assurance:Development of the Portuguese System for Teacher Education Accreditation

Abstract: The accreditation systems of higher education institutions and/or programmes are becoming a policy measure used to find a balance between their autonomy and public assurance concerning the quality of the qualifications they award. This article analyses, from the point of view of this balance of power, the process of development of the Portuguese accreditation system aimed at providing public assuranc e that initial teacher education programmes are more driven by social demand, namely by the changing school edu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 13 publications
0
5
0
1
Order By: Relevance
“…Although at the state level, in official documents, made quite specific proposals on the mechanisms needed to implement the new functions of education. This integration of learning and productive sphere, stimulating creativity, leadership and initiative, expanding organizational diversity and individual access to resources, education, focus on education throughout life and, as a consequence, the individualization of educational trajectories, the rejection of the culture of learning, creating a culture of productivity, creativity, innovation, dynamic configuration of the formed competences under a rapidly changing demand and production, a fundamental change in the role and tasks of teachers, the introduction of new technologies in education, including ICT, transparency, interaction with all social institutions of society, reducing the role of the state in education (Campos, 2004).…”
Section: The Study Of Problemmentioning
confidence: 99%
See 1 more Smart Citation
“…Although at the state level, in official documents, made quite specific proposals on the mechanisms needed to implement the new functions of education. This integration of learning and productive sphere, stimulating creativity, leadership and initiative, expanding organizational diversity and individual access to resources, education, focus on education throughout life and, as a consequence, the individualization of educational trajectories, the rejection of the culture of learning, creating a culture of productivity, creativity, innovation, dynamic configuration of the formed competences under a rapidly changing demand and production, a fundamental change in the role and tasks of teachers, the introduction of new technologies in education, including ICT, transparency, interaction with all social institutions of society, reducing the role of the state in education (Campos, 2004).…”
Section: The Study Of Problemmentioning
confidence: 99%
“…Thus, systemic changes in the external education environment and changes of internal relations of students, teachers, and parents require systemic changes in teacher education, the main structural components of the system of pedagogical education: objectives, content, forms and methods of training teachers (Miller & Taylor, 1993;Campos, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…The accreditation system implemented inseveral countries was also influenced by the American system (Chaiyaphumthanachok, Tangdhanakanond & Sujiva, 2016). Accreditation was adopted by international institutions (UNESCO, World Bank, OECD) over time (Campos, 2004). In teacher training, the accreditation system practices were based on National Council for Accreditation of Teacher Education (NCATE) activities in 1954.All pioneering nations in accreditation were convinced about implementation between 1989 and 2004 (Wise, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Literature review conducted on the accreditation studies in teacher training revealed that several studies were conducted on accreditation systems in various countries including Portugal (Campos, 2004), Thailand (Chaiyaphumthanachok, Tangdhanakanond, & Sujiv 2016), Turkey (Grossman, Sands & Brittingham, 2010), UK, USA, and Japan. Furthermore, different accreditation studies were conducted on accreditation reform in teacher training (Murray, 2000), accreditation policies (Ingvarson, Beavis & Kleinhenz, 2007), accreditation and accreditation experiences (Freeman, Simonsen, Briere, & Mac Suga-Gage, 2014;Vlasceanu, Grünberg & Parlea, 2007;Kavak, 1999;Uçar & Levent, 2017), scale development on perceptions towards accreditation (Semerci, 2017), the views of academicians on accreditation (Harvey, 2004), misunderstandings about accreditation (Murray, 2012), the review of national and international trends and applications in teacher training accreditation (Ingvarson, Elliott, Kleinhenz, & McKenzie, 2006;Yılmaz, 2016), and the benefits of accreditation and the problems experienced during the accreditation process (Türel & Altıntaş, 2018).However, there are no studies that aimed to determine the views of the participating academicians about the initial project conducted on teacher training accreditation in Turkish history.…”
Section: Introductionmentioning
confidence: 99%
“…de la ES mexicana es algo del uso cotidiano, en este uso regular conviene una reflexión sobre sus implicaciones. Al respecto, diversas investigaciones en México y en el mundo han referido a la tendencia de analizar la calidad educativa en este nivel de formación(Campos, 2004;Márquez, 2004; Alvarado, Morales y Aguayo, 2016; Mungaray, Ocegueda, Moctezuma y Ocegueda, 2016).A pesar de la orientación de las líneas de acción institucionales hacia la búsqueda de la calidad, poco se ha cuestionado el sentido de dicho concepto en este nivel educativo, salvo casos de algunas investigaciones(Egido, 2005;Gautier, 2007; Olaskoaga, Marúm y Partida, 2015). El tema de calidad en ES puede abordarse desde distintos enfoques, y es necesario especificar la postura bajo la cual las acciones educativas se fundamentan, debido a que el concepto suele diferir considerablemente dependiendo de la perspectiva que la soporta; y, en consecuencia, ello impacta en las acciones educativas que le derivan.…”
unclassified